2002
DOI: 10.1007/s00228-001-0407-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mycophenolic acid glucuronidation by niflumic acid in human liver microsomes

Abstract: The range of hepatic rate of MPA glucuronidation is narrow relative to those of ethinyloestradiol, testosterone and zidovudine glucuronidation obtained from literature. The Ki value of NA is one order of magnitude lower than the K(m) for MPA in non-inhibited samples. This indicates that the inhibitor affinity for glucuronosyl transferase is greater than that of the substrate. The range of variation of NA IC(50) values is narrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…The average K m determined for three HLM samples (0.082 mM) closely agrees with the average K m determined for three different preparations of 1A9 enzyme (0.077 mM). Estimates of apparent K m of HLM samples for MPA in other studies have generally ranged between 0.2 and 0.6 mM (Vietri et al, 2000(Vietri et al, , 2002Bowalgaha and Miners, 2001;Shipkova et al, 2001). However, Bernard and Guillemette (2004) reported lower K m values, closer to the estimates in our study (0.15-0.27 mM, with two sets of pooled human liver micro- FIG.…”
Section: Discussionsupporting
confidence: 81%
“…The average K m determined for three HLM samples (0.082 mM) closely agrees with the average K m determined for three different preparations of 1A9 enzyme (0.077 mM). Estimates of apparent K m of HLM samples for MPA in other studies have generally ranged between 0.2 and 0.6 mM (Vietri et al, 2000(Vietri et al, , 2002Bowalgaha and Miners, 2001;Shipkova et al, 2001). However, Bernard and Guillemette (2004) reported lower K m values, closer to the estimates in our study (0.15-0.27 mM, with two sets of pooled human liver micro- FIG.…”
Section: Discussionsupporting
confidence: 81%
“…The NSAIDs tested in this study also showed inhibitory potency against the glucuronidation of mycophenolic acid [13], which is reported to be catalysed mainly by UGT1A9 in the human liver [6]. Niflumic acid had a potent inhibitory effect on the glucuronidation of mycophenolic acid in human liver microsomes, and its IC 50 and K i values were 8 and 15 mm, respectively [13,14]. The affinities of niflumic acid and mycophenolic The substrate concentration of 4-methylumbelliferone was 5 mm.…”
Section: Discussionmentioning
confidence: 89%
“…proposed selective substrates and inhibitors of five major hepatic UGT isoforms and recommended inhibitor concentrations relative to their inhibition potency (IC 50 values). Examples of selective inhibitors are atazanavir for UGT1A1/1A3 (Zhang et al, 2005); hecogenin for UGT1A4 (Uchaipichat et al, 2006a,b;Walsky et al, 2012); troglitzone for UGT1A6 (Ito et al, 2001), digoxin, transilast, and niflumic acid for UGT1A9 (Vietri et al, 2002;Lapham et al, 2012); and b-phenyllongifolol-2 for 2B7 (Bichlmaier et al, 2007). Careful optimization of experimental conditions (Court, 2014;Zhou and Miners, 2014) (also more in Supplemental Materials) should be done for the selection of suitable inhibitor concentrations, e.g., when considering the presence of BSA, in particular for UGT1A9 and 2B7 reactions.…”
Section: Chemical Inhibitors Of Ugtmentioning
confidence: 99%